Design and Analysis of Wheel Electric Drive System with Gear Reducer of Single Trailing Arm - Xu Naiwen; Gu Cheng; Chen Xinbo (Jixie chuandong)
The structure of electric wheel drive system with gear reducer for single trailing arm suspension is designed.The structural components and assembly relation is illustrated in detail.And the specialty is the motor for this system is placed on the frame.The mechanism of gear transmission and the gearbox,single-trailing arm and frame consist of a four-bar mechanism.The kinetic principle of this mechanism is explained.This four-bar mechanism make the center distance between motor and wheel is variable and ensure the feasibility of the designed structure for electric wheel drive system.At last,the model is established in ADAMS for simulation and prove the superiority of designed system.The proposed structure reduces the unsprung mass of vehicles effectively and improves the ride comfort and wheel ground adhesion for vehicle.